Synthesis, growth and characterization of a nonlinear optical crystal: l-Leucinium perchlorate - P. Baskaran; M. Vimalan; P. Anandan; G. Bakiyaraj; K. Kirubavathi; K. Selvaraju (Journal of Taibah University for Science, 2017)
An amino acid based semiorganic nonlinear optical family single crystal of l-leucinium perchlorate (LLPCl) was grown by the solvent evaporation method at ambient temperature. Good optical quality single crystals up to a size of 6 mm × 5 mm × 3 mm were obtained. The single-crystal XRD analysis shows that the grown crystals have a monoclinic structure. Fourier transform infrared (FTIR) spectral analysis and UV–vis spectral studies were also carried out. Microhardness mechanical studies show that the hardness number (Hv) of a LLPCl single crystal decreases with the load as measured by the Vickers microhardness method. The dielectric properties of the grown crystal were analysed by varying the frequency. Photoconductivity analysis gives the variation of the photocurrent and dark current. The nonlinear optical properties were studied using the Kurtz and Perry powder method and the second harmonic generation efficiency was found to be 2.6 times higher than that of KDP crystals.